HAMBATAN KOMUNIKASI DALAM PEMBELAJARAN ONLINE DI MASA PANDEMI COVID-19 - Rindana Intan Emeilia; Arina Muntazah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2021)
This study aims to analyze and explain communication barriers between teachers and students in the implementation of online learning activities. The study uses qualitative descriptive methods, which use analytical data from interviews and observation of the object. The COVID-19 situation has made the world of education stop temporarily for teaching and learning activities in advance in order to stop the spread of the COVID-19 virus by replacing online teaching and learning activities conducted at homeOnline learning using digital media presents new barriers in the process of communicating between teachers and students. The study was conducted by interviewing teachers and students online regarding communication barriers found during online learning. Based on the results of the research. the obstacles found are; communication saturation, limited interpersonal communication, limited space and time in learning activities, reduced student confidence, limitations of technology and information, the emergence of feelings of loneliness, media limitations, fatigue of online communication and limitations of media literacy.